Zollinger Ellison Syndrome in a Patient with Multiple Endocrine Neoplasia Type 1: A Classic Presentation - Ishani Shah; Neil Vyas; Kambiz S. Kadkhodayan (Case Reports in Gastrointestinal Medicine)
Zollinger Ellison Syndrome (ZES) is characterized by a wide spectrum of conditions including severe gastroesophageal reflux disease, peptic ulcer disease, watery diarrhea, and weight loss. We present a case of a 60-year-old woman being evaluated for severe dyspepsia, vomiting, and chronic diarrhea, who was diagnosed to have ZES associated with a pancreatic neuroendocrine tumor, in the setting of multiple endocrine neoplasia (MEN) type 1. Although cases of ZES have been reported previously, we believe that our case is a classic presentation of ZES diagnosed on the basis of typical radiologic, endoscopic, and endosonographic features.